Robust gain-scheduled autopilot design for spin-stabilized projectiles with a course-correction fuze - Theodoulis, Spilios; Sève, Florian; Wernert, Philippe (Aerospace science and technology, 2015)
This article explores the design of a pitch/yaw axis load factor autopilot for a class of 155-mm spin-stabilized ammunition which incorporates a novel nose-positioned course correction fuze system used for trajectory correction. The projectile full nonlinear model is discussed and a procedure for obtaining the system q-LPV model necessary for control synthesis is exposed. Important properties relevant to axis cross-coupling, internal modes and stability properties specific to this kind of system are also highlighted. A comparison of full- and reduced-order mixed-sensitivity H∞ linear compensators with an additional model following constraint for the design of the projectile autopilot is presented. Robust stability with respect to aerodynamic and actuator/sensor modeling uncertainties is verified via standard μ-analysis tools throughout the projectile flight envelope. Nonlinear 7-DoF trajectory simulation results are finally presented for a single or dual control surface actuator configuration.